Comparison of positron emission tomography/computed tomography with classical contrast-enhanced computed tomography in the initial staging of Hodgkin lymphoma. Issue 2 (February 2015) - Bednaruk-Młyński, Ewa; Pieńkowska, Joanna; Skórzak, Adam; Małkowski, Bogdan; Kulikowski, Waldemar; Subocz, Edyta; Dzietczenia, Justyna; Zalewska, Marta; Leśniewski-Kmak, Krzysztof; Zaucha, Renata; Wróbel, Tomasz; Zaucha, Jan M.
Abstract We compared initial computed tomography (CT) and positron emission tomography (PET)/CT in 96 patients with Hodgkin lymphoma (HL), assessing the role of baseline PET/CT in stage migration and treatment selection. The number of patients with stage I, II, III and IV disease based on CT versus PET/CT was: 5 vs. 7, 49 vs. 37, 28 vs. 22 and 14 vs. 30, respectively. In 33 (34%) patients, PET/CT changed HL stage: 27 (28%) were upstaged and six (6.3%) downstaged. Upstaging was caused by detection of new extranodal involvements (47 sites in 26 patients): bone marrow (10 patients), spleen (five patients) and lung (two patients). In nine patients ≥ 2 further coexisting locations were detected. Downstaging resulted from the absence of fluorodeoxyglucose (18F-FDG) uptake in enlarged nodes (> 15 mm) in the abdomen and pelvis. PET/CT modified HL stage in 34% of patients leading to treatment modification in the majority. Our results indicate that PET/CT should be mandatory in the initial staging of HL.